FACTORS CONTRIBUTING TO YOLK RETENTION IN POULTRY: A REVIEW - K. A. Khan, S. A. Khan, A. Aslam, M. Rabbani1 and M.Y. Tipu (Pakistan Veterinary Journal, 2004)
Yolk retention and yolk sac infection is considered as an important cause of death in chicken as well as in guinea fowl, duck, turkey, quail and goose. The factors which slow down the rate of yolk absorption and may in turn, lead to yolk retention are discussed. Yolk sac infection of bacterial origin is most important among these factors. Other factors which may contribute include posthatch starvation, type of initial feed, brooding temperature, prolonged exposure to hatcher environment and size of birds.